ANALISIS UNSUR INSTRINSIK DALAM CERPEN BERJUDUL “SETANGKAI POHON IBU” KARYA VAUGHAN CALLISTA, V.P - NIA, IKA; SUDRAJAT, ROCHMAT TRI; -, LATIFAH (IKIP Siliwangi, 2020)
The short story is a fictional narrative with a length of about 500 to 10,000 words and is more focused than a novelet, short stories tend to be short, mostly only telling a single incident, but still paying attention to the elements in it such as themes, characters, plot, background, characterization, message and style of language. The short story